Study on the Hepatoprotective Effect of Oyster Mushroom (Pleurotus Florida) Against Paracetamol Induced Liver Damage in Wistar Albino Rats - Sumy, Afroza Khanam; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2011)
Background: Liver damage can be occurred due to prolonged use of higher doses of some drugs, exposure to some chemicals or infectious agents. But liver protective drugs are not available in modern medicine. Some hepatoprotective herbal medicines are often used in the treatment of liver damage. Objective: This experimental study was carried out to observe the hepatoprotective effect of Oyster mushroom (Pleurotus florida) against paracetamol induced liver damage in Wistar albino rats. Method: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st July 2009 to 30th June 2010. A total number of 34 Wistar albino rats, age ranged from 90 to 120 days, weighing between 150 to 210 grams were selected for the study. After acclimatization for 14 days, they were divided into two groups, control group (Group A) and experimental group (Group B- mushroom pretreated and paracetamol treated group). Control group again subdivided into group A1 (baseline control) and group A2 (paracetamol treated control group). All groups of animals received basal diet for 30 consecutive days. Group A1 consisted of 10 rats, received propylene glycol (2 ml/kg bw, orally) only on 30th day. Group A2 consisted of 14 rats, received single dose of paracetamol suspension (750 mg/ kg bw, orally) only on 30th day. Group B consisted of 10 rats, received mushroom extract (200 mg/ kg bw, orally) for 30 consecutive days and paracetamol suspension (750 mg/ kg bw, orally) only on 30th day. All the animals were sacrificed on 31st day. Then blood and liver samples were collected. Initial body weight, final body weight and liver weight were measured. Then measurement of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in serum and assessment of malondialdehyde (MDA) concentration in liver tissue homogenate were done by using standard laboratory kits. The statistical analysis was done by one way ANOVA and Bonferroni test as applicable. Result: The mean serum AST, ALT levels and in the liver tissue MDA concentration were significantly (p<0.001) higher in paracetamol treated group in comparison to those of baseline control group. Again, the mean serum AST (p<0.05), ALT (p<0.05) levels and in the liver tissue homogenate MDA concentration (p<0.001) were significantly lower in mushroom pretreated and paracetamol treated group (experimental group) when compared to those of only paracetamol treated group (control). Conclusion: This study reveals that Oyster mushroom (Pleurotus florida) which is excellently edible and nutritious, may have some hepatoprotective role. Key words: hepatoprotective; oyster mushroom; malondialdehyde; tissue homogenate DOI: 10.3329/jbsp.v5i2.6776 J Bangladesh Soc Physiol. 2010 December; 5(2): 46-52